Light-responsive rotaxane-based materials: inducing motion in the solid state - Saura-Sanmartin, Adrian (Beilstein Journal of Organic Chemistry, 2023)
Light-responsive rotaxane-based solid-state materials are ideal scaffolds in order to develop smart materials due to the properties provided by the mechanical bond, such as control over the dynamics of the components upon application of external stimuli. This perspective aims to highlight the relevance of these materials, by pointing out recent examples of photoresponsive materials prepared from a rotaxanated architecture in which motion of the counterparts and/or macroscopic motion of the interlocked materials are achieved. Although further development is needed, these materials are envisioned as privileged scaffolds which will be used for different advanced applications in the area of molecular machinery.
Keywords: light irradiation; light-responsive materials; mechanical bond; mechanically interlocked materials; rotaxanes